Pneumococcal 23B Molecular Subtype Identified Using Whole Genome Sequencing. (10th May 2017) - Kapatai, Georgia; Sheppard, Carmen L.; Troxler, Lukas J.; Litt, David J.; Furrer, Julien; Hilty, Markus; Fry, Norman K.
Abstract: The polysaccharide capsule is a major virulence factor of Streptococcus pneumoniae and the target of all currently licensed pneumococcal vaccines. At present, there are 92 serologically distinct pneumococcal serotypes. Structural and antigenic variation of capsular types is the result of genetic variation within the capsular polysaccharide synthesis (CPS) locus; however, genetic variation may not always result in phenotypic differences which produce novel serotypes. With the introduction of high throughput whole genome sequencing, discovery of novel genotypic variants is not unexpected and this study describes a novel variant of the serotype 23B CPS operon. This novel variant was characterized as a novel genotypic subtype (23B1) with ∼70% homology to the published 23B CPS sequence. High sequence variability was determined in eight cps genes involved in sugar biosynthesis. However, there was no distinction between the classic 23B serotype and 23B1 serologically or in terms of polysaccharide structure. Phylogenetic and eBURST analysis revealed a distinct lineage for 23B1 with multiple clones (UK, Thailand, and USA) that arose at different points during pneumococcal evolution. Analysis of the UK S. pneumoniae isolates ( n  = 121) revealed an upsurge of 23B1 ST2372 in 2011, after which this previously unseen ST increased to reach 50% proportion of the 23B sequenced isolates from 2013 and remained prevalent within our sequenced isolates from later years. Therefore, although the 23B1 variant appears to have no phenotypic impact and cannot be considered as novel serotype, it appears to have led to a genetic restructuring of the UK serotype 23B population.